1995
DOI: 10.1016/0005-2736(95)00104-b
|View full text |Cite
|
Sign up to set email alerts
|

Relation between membrane fluidity and signal transduction in the human megakaryoblastic cell line MEG-01

Abstract: The fluidity of the plasma membrane is thought to affect the responsiveness of blood platelets. We measured membrane fluidity in a single cell by Fluorescence Recovery after Photobleaching (FRAP) of the lipophilic probe DiIC14. Since platelets are too small for this technique, we used the human megakaryoblastic cell-line MEG-01, which shares many properties with platelets. MEG-01 cells were cultured for 44 h with simvastatin or mevalonate to change the cholesterol content, enabling analysis of signal processin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Associated with such changes in membrane lipid composition, blood platelets have been demonstrated to become more sensitive to aggregation induced by adrenalin or ADP [58][59][60][61][62]. On the other hand, there are reports showing that the interaction of protein and peptide ligands with platelet membrane receptors leads to the changes in the organisation of membrane components, and such displacements in membrane protein projection could be mediated by the alterations of membrane lipid fluidity [43,54,59,[63][64][65][66].…”
Section: Membrane Lipid Fluiditymentioning
confidence: 99%
See 2 more Smart Citations
“…Associated with such changes in membrane lipid composition, blood platelets have been demonstrated to become more sensitive to aggregation induced by adrenalin or ADP [58][59][60][61][62]. On the other hand, there are reports showing that the interaction of protein and peptide ligands with platelet membrane receptors leads to the changes in the organisation of membrane components, and such displacements in membrane protein projection could be mediated by the alterations of membrane lipid fluidity [43,54,59,[63][64][65][66].…”
Section: Membrane Lipid Fluiditymentioning
confidence: 99%
“…The relation between platelet membrane fluidity and signal transduction in human platelets remains indefinable, however, the fluidity of platelet plasma membranes is thought to effect the responsiveness of blood platelets [43,59,[67][68][69][70][71][72]. The impaired macromolecular interactions in membrane, associated with the reduced diffusion of various membrane components, are believed to modulate cell receptor-mediated signal transduction [47].…”
Section: Role In Intracellular Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased phosphatidylcholine unsaturation, which results in more fluidity, increases the activity of protein kinase C29; in contrast, higher cholesterol:phospholipid ratios in the plasma membrane (a more rigid membrane) increase cyclic AMP concentrations in megakaryoblasts 30…”
Section: Lcpufa In the Retinamentioning
confidence: 99%
“…In line with such a suggestion we revealed a significant correlation between the reduced platelet membrane fluidity and more intense calcium mobilization in diabetic platelets. The relationship between the dynamic parameters of cell membrane lipid bilayer, calcium mobilization and cell activation was validated earlier with the use of various modulators of membrane lipid fluidity (25)(26)(27)(28), which have been reported to inhibit spontaneous Ca2+ release in numerous cell types, probably due to their direct interaction with a Ca2+ channel rather than with other permeability pathways (29)(30)(31). In our earlier studies we also reported that the preventive effects of procaine on platelet release reaction and calcium mobilization might relate to the changes in the organization of membrane components embedded into a lipid bilayer, which are crucial in triggering of platelet release reaction.…”
Section: Discussionmentioning
confidence: 95%